نظام المياه الجوفية الحرة في المنطقة الواقعة بين نهري الصنوبر والكبير الشمالي (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2014)
يتضمن البحث دراسة تغيرات مناسيب المياه الجوفية الحرة مع الزمن، ومدى تأثرها بالعوامل الطبيعية والاصطناعية، الأمر الذي يسمح بتقويم الوضع المائي العام للطبقة المائية. تبين من خلال هذه الدراسة أن نظام المياه الجوفية في منطقة الدراسة من نوع خط التقسيم المائي (النظام المناخي) يرتبط ارتباطاً مباشراً بالرشح من الهطولات المطرية، حيث تلعب العوامل الطبيعة (التغذية الراشحة) الدور   الرئيس في تشكل نظام المياه الجوفية، إضافةً إلى العوامل الاصطناعية (الري)، وهذه العوامل تُنتج ثلاث فترات في التغيرات الفصلية الواضحة للمناسيب في السنة الهيدرولوجية (هبوط، ثبات، نهوض). كما أن المياه الجوفية متجددة نتيجة الاستقرار في أوضاع مناسيب هذه المياه، وهي تنصرف تبعاً للشبكة الهيدروديناميكية للمياه الجوفية في نهري الكبير الشمالي والصنوبر وفي البحر المتوسط أيضاً.This is a study of free groundwater level changes through time, and the level of its being affected by natural and artificial factors, which allows evaluating general water situation of the aquifer. This study shows that groundwater system in the study area from the type of water division line (climatic system) connects in direct connection with infiltration from rainfalls in which the natural factors (recharge) play the main role in forming the system of groundwater, in addition to the artificial factors (irrigation), and these factors yield three periods of the obvious terminal changes of the levels in hydrologic year (descending, stability, ascending). However, groundwater is renewable because of stability in the situations of this water, and its discharge to hydrodynamic net of groundwater in Al-kabir al-shimali and Al-snobar rivers and in the Mediterranean Sea as well.